Komposisi Musik Semarak Sipai Bersumber Dari Beruji Dol Dalam Upacara Tabot Di Kota Bengkulu - Sandy Purwanda; desmawardi desmawardi; Asep Saepul Haris (Jurnal Musik Etnik Nusantara, 2024)
Music is a means of expressing the soul to communicate and interact between living creatures. Through music we can express various ideas with various colors of sound produced by any object that can accommodate the idea itself. Sounds and voices are arranged well so that a musical work is created as a harbor for ideas that are full of messages and meaning. This work begins with research on the Bruji Dol performance and from the results of the analysis, a conclusion is drawn to take one part, namely the song Girik" which is contained in the Bruji Dol performance in the Tabot ceremony in the city of Bengkulu. Beruji dol is a depiction of the spirit of war carried out by two groups, namely Tabot Bangsal and Tabot Imam. Beruji dol has an interesting musical case, namely that there is a game concept that is "freely bound" in the tasa game of the Tamatam repertoire called "Girik". To create the musical composition "Semarak Sipai" it was worked on using the Analytical Descriptive method using a Re-interpretation of Tradition approach. Through the creation of the musical composition "Semarak Sipai", the creator tried to present several forms of novelty in various aspects of the work in accordance with the concept offered. The Tradition Re-interpretation approach is used to share musical experiences as a contribution to the development of the musical composition itself.